Ethical and Islamic perspectives of biotechnology research and human consumption of genetically modified organisms - Ansari, Abdul Haseeb; Jamal, Parveen (Hamdard Foundation Pakistan, 2017)
The Sanitary and Phytosanitary Agreement of 1992, which is a part of the WTO legal regime, in order to ensure augment international trade in GMOs, provides for ensuring their safety so that they could be acceptable in international market, i.e. it prescribes for a kind of precautionary principle, which is supposed to be adhered to by the WTO Member States. This is well in practice. But some jurists and environmentalists find it trade friendly, which can be detrimental to human health and the environment. Moreover, states, which produce GMOs, like to introduce it quickly; and for that, they perform some kind of risk assessment, which were not be acceptable to some importing countries. This resulted in disputes, which were ultimately resolve, in most of the cases in favour of international trade rather than protection of the environment or ensuring human health, except for where the harm was eminent. Keeping this in mind, the paper conducts a critical appraisal of the PP provisions of the SPS Agreement and offers certain amicable suggestions for improvement on the existing provisions.